Designing the UI/UX of a Mobile-Based Library Catalog Application for the XYZ Community Using the Design Thinking Method - Faza Bilwildi Emyu; Sarah Astiti (Universitas Islam Kuantan Singingi, 2026)
The XYZ Community library maintained a collection of over 800 book titles yet relied entirely on manual catalog management, which substantially impeded members from efficiently discovering and accessing available resources. This study designed a mobile-based library catalog application UI/UX for XYZ Community members by applying the Design Thinking method across five iterative stages: Empathize, Define, Ideate, Prototype, and Test. In the Empathize stage, data were collected through interviews and observations involving 20 community members. The Define stage produced problem statements derived from Point of View and How Might We frameworks. The Ideate stage produced 12 priority features derived from identified user pain points through participatory brainstorming. A high-fidelity prototype comprising six primary screens Splash Screen, Onboarding, Home, Catalog, Book Detail, and About Us was developed using Figma. Usability evaluation using the System Usability Scale (SUS) administered to 30 respondents yielded a mean score of 82,7, classified as Excellent (Grade B). All respondents confirmed that the interface was easy to learn and operate, and the prototype is deemed ready for the implementation stage.